Q: Does y equals 3x2 plus 2x-3 represent a function?

Write your answer...

Submit

Still have questions?

Continue Learning about Math & Arithmetic

If x = -7, then x3 = -343 so that 2x3 = -686 y = 2 then 15 y = 30 So 2x3 + 15y = -686 + 30 = -656

It can be simplified in the form of: 2x3+9x2-7x-34 = 0

x = -7, y = 2 ⇒ 2x3 + 15y = 2 x (-7)3 + 15 x 2 = 2 x (-343) + 15 x 2 = -656

2x3 + 4 = 17 2x3 = 13 x3 = 13 / 2 x = (13 / 2)1/3 x = 521/3 / 2

Rearrange: 4x5 + 6x2 + 6x3 + 9 Group: 2x2 (2x3 + 3) + 3 (2x3 + 3) Simplify to get your answer: (2x2 + 3) (2x3 + 3)

Related questions

Not necessarily.

If x = -7, then x3 = -343 so that 2x3 = -686 y = 2 then 15 y = 30 So 2x3 + 15y = -686 + 30 = -656

(2x3)+(3x5)-(3x2)= 2x3=6 3x5=15 3x2=6 So..... 6x25-6= 6x25=150 150+6=156

your equation is this... 2x3 + 11x = 6x 2x3 + 5x = 0 x(2x2 + 5) = 0 x = 0 and (5/2)i and -(5/2)i

It can be simplified in the form of: 2x3+9x2-7x-34 = 0

It depends on whether or not there are parentheses around the 2x3. If yes, the answer is 26. If not, the answer is 48.

x = -7, y = 2 ⇒ 2x3 + 15y = 2 x (-7)3 + 15 x 2 = 2 x (-343) + 15 x 2 = -656

2x3 + 4 = 17 2x3 = 13 x3 = 13 / 2 x = (13 / 2)1/3 x = 521/3 / 2

Rearrange: 4x5 + 6x2 + 6x3 + 9 Group: 2x2 (2x3 + 3) + 3 (2x3 + 3) Simplify to get your answer: (2x2 + 3) (2x3 + 3)

13

2x+3=9x-2x -2x3=7x/7 /73/7=x

4 equals 2x2, 6 equals 2x3